Madame Bovary [videorecording (DVD)] - Wasikowska, Mia, 1989-; Miller, Ezra; Carmichael, Laura, 1986-; Giamatti, Paul; Flaubert, Gustave, 1821-1880 (Alchemy, 2015)
Desperate to escape the dullness of provincial life, a young married woman pursues forbidden fantasies through a series of indiscreet seductions and adulterous affairs. Based on the acclaimed novel that transformed the Romantic era.